Auraptene inhibits migration, invasion and metastatic behavior of human malignant glioblastoma cells: An in vitro and in silico study - Mousavi, Seyed Hadi; Jalili-Nik, Mohammad; Soukhtanloo, Mohammad; Soltani, Arash; Abbasinezhad-Moud, Farzaneh; Mollazadeh, Hamid; Shakeri, Farzaneh; Bibak, Bahram; Sahebkar, Amirhossein; Afshari, Amir R (Avicenna journal of phytomedicine, 2024)
The present work examined the anti-metastatic effects of auraptene and their underlying mechanisms of action in U87 Glioblastoma multiforme (GBM) cells. To test the hypothesis, cell culture, Matrigel invasion assay, scratch wound healing assay, gelatin zymography assay, qRT-PCR, and western blot experiments were conducted. At sublethal concentrations of 12.5 and 25 µg/ml, auraptene exhibited a significant reduction in cell invasion and migration of U87 cells, as assessed using scratch wound healing and Transwell tests, respectively. The qRT-PCR and zymography experiments demonstrated a significant decrease in both mRNA expression and activities of MMP-2 and MMP-9 following auraptene treatment. Western blot analysis also showed that MMP-2 protein level and phosphorylation of metastasis-related proteins (p-JNK and p-mTOR) decreased in auraptene-treated cells. Molecular docking studies consistently demonstrated that auraptene exhibits a significant affinity towards MMP-2/-9, the ATP binding site of mTOR and JNK1/2/3. Auraptene inhibited the migration and invasion of GBM cells. This inhibitory effect was induced by modulating specific mechanisms, including suppressing MMPs, JNK, and mTOR activities.